Project-Based Learning Using Podcast-Assisted Media in the Teaching of English Speaking Skill - Ma'rufah, Anis; Samanhudi, Udi; Ardiasih, Lidwina Sri (Lectura : Jurnal Pendidikan, 2024)
Developing speaking skill is difficult for foreign language teachers and learners since they rarely use the target language outside the classroom. However, students need more opportunities and confidence to use it outside the classroom. Thus, teachers must adopt various teaching methods to strengthen the students’ speaking skill in English. Nowadays, students must possess competencies relevant to the 21st century, such as analysis and problem-solving, creativity and invention, communication, teamwork, life skills, and efficient use of technology. Therefore, Project-Based Learning (PjBL) provides opportunities to learn deep content knowledge and 21st-century skills. One of the methods used is using Podcast. A podcast is an up-to-date technology for improving students’ listening and speaking abilities. This qualitative study intends to determine the implementation of project-based learning using podcast-assisted media in teaching English speaking skill at one of the schools in Mojokerto, East Java, and the student’s perspective on it. The research participants were grade XI Science students. The data were collected through observation and interview. The data were analyzed using an analysis flow by Miles and Huberman which included data reduction, displaying the data, and a conclusion. This study showed that implementing project-based learning using podcast-assisted media in teaching English speaking skill ran smoothly. Students responded enthusiastically. At last, the students’ perspectives are also positive since Podcast-assisted media is able to enrich not only their speaking skill but also develop other language skills.